Strategic Knowledge Management for Institutional Effectiveness in Construction Procurement: The Role of Stakeholder Inter-Communication - El Asri, Hayat; Agnaou, Abderrahim; Nouamani , Said (Journal of Knowledge Management Practice, 2025)
In the construction industry, knowledge management and knowledge sharing face significant challenges, primarily due to the involvement of diverse stakeholders and the transient nature of work clusters. While technical issues often receive attention, the informal transfer of knowledge from previous projects remains a critical gap, as the preservation of intellectual capital is essential for organizational effectiveness. The dynamic nature of construction projects, with their numerous stakeholders, further complicates the development of efficient knowledge-sharing practices. As a result, construction organizations often struggle to retain valuable insights from past projects, leading to inefficiencies and a lack of continuity in decision-making. To address these challenges, various knowledge management strategies are being explored. This research paper specifically examines knowledge management within construction procurement in Morocco's public sector, presenting a comprehensive and integrated framework validated by industry experts. The proposed framework is designed to empower procurement teams to effectively leverage organizational knowledge, thereby promoting more efficient and informed decision-making and enhancing overall institutional effectiveness. The framework also emphasizes the role of effective inter-communication among stakeholders, which is crucial for fostering a culture of knowledge sharing and ensuring that all parties can contribute to the continuous improvement of procurement practices.
Keywords: knowledge management; knowledge sharing; KM framework; institutional effectiveness; procurement